Variations in competencies needed to complete surgical training. Issue 6 (1st August 2019) - Wood, S.; James, O. P.; Hopkins, L.; Harries, R.; Robinson, D. B. T.; Brown, C. M.; Abdelrahman, T.; Egan, R. J.; Lewis, W. G.
Abstract : Background: This study aimed to analyse the degree of relative variation in specialty‐specific competencies required for certification of completion of training (CCT) by the UK Joint Committee on Surgical Training. Methods: Regulatory body guidance relating to operative and non‐operative surgical skill competencies required for CCT were analysed and compared. Results: Wide interspecialty variation was demonstrated in the required minimum number of logbook cases (median 1201 (range 60–2100)), indexed operations (13 (5–55)), procedure‐based assessments (18 (7–60)), publications (2 (0–4)), communications to learned associations (0 (0–6)) and audits (4 (1–6)). Mandatory courses across multiple specialties included: Training the Trainers (10 of 10 specialties), Advanced Trauma Life Support (6 of 10), Good Clinical Practice (9 of 10) and Research Methodologies (8 of 10), although no common accord was evident. Discussion: Certification guidelines for completion of surgical training were inconsistent, with metrics related to minimum operative caseload and academic reach having wide variation. Abstract : Certification guidelines for completion of surgical training are inconsistent and demonstrate significant interspecialty variance. Consensus regarding the competencies required for independent surgical practice is required urgently. Curricular harmonization needed Abstract : Antecedentes: Este estudio se propuso analizar el grado de variación relativa en las competencias específicas de la especialidad que se requieren para obtener el certificado de haber completado la formación ( Certification of Completion of Training, CCT) por el Joint Committee for Surgical Training (JCST) del Reino Unido. Métodos: Se analizaron y compararon las guías del organismo regulador relacionadas con las competencias en habilidades quirúrgicas, tanto operatorias como no operatorias, requeridas para el CCT. Resultados: Se demostró una amplia variación entre especialidades en el número mínimo requerido del cuaderno de casos (mediana 1.201; rango 60‐2.100), operaciones índices (13; 5‐55), evaluaciones basadas en procedimientos (18; 7‐60), publicaciones (2; 0‐4), comunicaciones para determinar asociaciones (0; 0‐6) y auditorias (4; 1‐6). Los cursos obligatorios entre las distintas especialidades incluían: formación de los formadores (10 de 10 especialidades), apoyo vital avanzado en traumas (6/10), buena práctica clínica (9/10) y metodologías clínicas (8/10), aunque era evidente que no existía un acuerdo común. Conclusión: Las directrices sobre la certificación para completar la formación quirúrgica eran inconsistentes, con una amplia variación en los números relativos a los mínimos casos operados y objetivos académicos alcanzados.